Male Genital Mutilation in the Name of Ritual Circumcision: A Case Report and Literature Review - Latif Dar; Alhareth Baarimah; Saeed Alshehrani; Alhassan Alasiri; Mohammad Alassiri; Saleh Al-Ghamdi (Case Reports in Urology)
Unlike female genital mutilation, the alteration of male genitals has not received much attention. Circumcision is the most common and oldest surgical procedure being performed. When performed by surgeons or well-trained personal the procedure is safe, but most of the times it is being performed by untrained people with no or little medical background. This has led to many complications. Total skin loss is an uncommon but serious complication. There is an ongoing debate regarding the management of this complication. Here, we present a case of total penile skin loss which had resulted from penile mutilation in the name of ritual circumcision.